Alabama Wildlife, Volume 5 - Shelton-Nix, Ericha (Book collections on Project MUSE., 2017)
Alabama Wildlife, Volume 5 offers a comprehensive update and provides a wealth of new information concerning changes and developments relative to the conservation status of wild animal populations of the state that have occurred in the decade since publication of the previous four volumes in 2004. Enhancements include the addition of any new or rediscovered taxon, species priority status changes, and taxonomic changes, plus the addition of the crayfishes, which were left out previously because so little was known about these understudied taxa. A complete taxonomic checklist is included, which lists each imperiled taxon along with its priority designation followed by detailed species accounts. The eighty-four crayfish species accounts are comprised of a physical description (including a photograph, when available), distribution map, habitat summary, key life history, ecological information, basis for its status classification, and specific conservation and management recommendations. This revised expansion of the Alabama Wildlife set will be helpful to those seeking to broaden their knowledge of Alabama's vast wildlife resources and will greatly influence future studies in the conservation of many of the imperiled species. The University of Alabama Press originally released a set of four volumes titled Alabama Wildlife in 2004. The series consisted of A Checklist of Vertebrates and Selected Invertebrates (Volume 1), Imperiled Aquatic Mollusks and Fishes (Volume 2), Imperiled Amphibians, Reptiles, Birds, and Mammals (Volume 3), and Conservation and Management Recommendations for Imperiled Wildlife (Volume 4). However, Alabama Wildlife, Volume 5 offers an all-inclusive and complete update of these four previously published volumes, making it the single resource required for all those working with or interested in Alabama's wild animals.